Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.